1999
DOI: 10.1093/jmt/36.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Music Exposure and Criminal Behavior: Perceptions of Juvenile Offenders

Abstract: The purpose of this investigation was to examine young offenders' perceptions of the relationship between exposure to music and their criminal behavior. Using a tool designed for the study, male felony offenders ages 12 to 17 were questioned about their music listening patterns and the perceived influence of listening on their offending fantasies and behavior. Rap music was the predominant choice across all participant profiles. While 72% of respondents believed that music influenced the way they feel at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
15
0
3
Order By: Relevance
“…First, the results of this study suggested that the implemented multimodal arts therapy intervention was useful in correctional setting to bring about appropriate behavioral changes among the participants during the intervention-a decrease of the frequency of aggressive behavior. Also, Cleveland (1992) found that an improvisational theater program, and Gardstrom (1999) suggest that music therapy intervention, may demonstrate a decrease in violence for the program participantsjuvenile delinquents. Secondly, the present results showed that emotional and conduct problems measured by the SDQ decreased during intervention.…”
Section: Resultsmentioning
confidence: 99%
“…First, the results of this study suggested that the implemented multimodal arts therapy intervention was useful in correctional setting to bring about appropriate behavioral changes among the participants during the intervention-a decrease of the frequency of aggressive behavior. Also, Cleveland (1992) found that an improvisational theater program, and Gardstrom (1999) suggest that music therapy intervention, may demonstrate a decrease in violence for the program participantsjuvenile delinquents. Secondly, the present results showed that emotional and conduct problems measured by the SDQ decreased during intervention.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, and that rap is a preferred genre by many of our clients, it is an integral focus of music therapy. The use of rap in music therapy requires a deep respect and understanding of rap history as an art form (Gardstrom, 1999;Tyson, 2002). Tyson came from a social work background and arguably is one of the first writers who brought to light the therapeutic benefits of hip-hop and rap, followed by several from the field of music therapy (Bednarz & Nikkel, 1992;Borling, 2017;Gallagher & Steel, 2002;Mössler, Chen, Heldal, & Gold, 2011;Gold et al, 2009;Gold et al, 2013;Vega, 2017;Viega, 2012).…”
Section: Vocal Recordingmentioning
confidence: 99%
“…As Zillmann (1979) argued, "Exposure of the annoyed individual to materials featuring hostile and aggressive behavior perpetuates his or her elevated state of excitation" (p. 321). Gardstrom (1999) observed that an aroused state and exposure to heavy-metal and rap music contribute to negative attitudes and aggressive behavior.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%